Functionalized Calix(4)nanocones - Haidisch, Anika; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2025)
The interest in synthesizing conjugated nanobelts (CNBs) and nanocones has increased recently. Although a number of various structures have been achieved, almost none have additional functional groups at the peripheral rims. Based on a calix[4]arene, a functionalized calix[4]nanocone was synthesized. Due to its rigid structure in combination with methoxy groups on both the upper and the lower rim, the nanocone was tested for the binding of alkaline ions in solution by NMR measurements. The nanocone shows a high selectivity for binding Na+ in favor of Li+ and K+ in CDCl3. By comparing the nanocone with a related but structurally flexible methoxy calix[4]arene, the impact of structural rigidity on selectivity is clearly demonstrated.